A contribution toward understanding the biospherical significance of Antarctic ozone depletion - Lubin, Dan; Mitchell, Greg; Frederick, John E.; Alberts, Amy D.; Booth, C. R.; Lucas, Timothy; Neuschuler, David (1992)
The paper presents and compares measurements of biologically active UV radiation made by the NSF scanning spectroradiometer (UV-monitor) at Palmer Station, Antarctica, during the Austral springs of 1988, 1989, and 1990. Column ozone abundance above Palmer Station is computed from these measurements using a multiple wavelength algorithm. Two contrasting action spectra are employed to estimate the biologically relevant dose from the spectral measurements: a standard weighting function for damage to DNA, and a new action spectrum representing the potential for photosynthesis inhibition in Antarctic phytoplankton. The former weights only UV-B wavelengths (280-320 nm) and gives the most weight to wavelengths shorter than 300 nm, while the latter includes large contributions out to 355 nm. Ozone abundances and dose-weighted irradiances provided by the NSF UV-monitor are used to derive the radiation amplification factors for both DNA- and phytoplankton-effective irradiance.